Development of a Minimum Reporting Set of Contextual Factors for Rehabilitation Studies: A Delphi Study - Boya Nugraha; Grace Engen; Cecilie Roe; Marit Kirkevold; Helene L Soberg; Nada Andelic; Christoph Gutenbrunner (Medical Journals Sweden, 2022)
Objective: To identify the most important categories of the International Classification of Service Organization in Rehabilitation (ICSO-R 2.0) for a minimum reporting data set. Methods: A 2-step Delphi survey was used. Rehabilitation experts from all world regions including physicians, nurses, neuropsychologists, physiotherapists, and others, were invited to participate. In the first round, all participants were asked to rate the categories and subcategories of the ICSOR 2.0 with the following criteria: Being relevant for study outcomes; Being distinctive among different rehabilitation settings; Being feasible to use and reported by objective figures or other clear characterization. All categories that were rated relevant, distinctive and feasible by more than 60% of respondents from the first round were included in the second round. Results: The most important and relevant factors for the minimum reporting set in rehabilitation services regarding the provider were: human resources, context, technical resources, quality assurance and management, location of provider, and ownership. Regarding the service delivery, the most important and relevant factors were: target group, rehabilitation team, aspect of time and intensity, setting, location of service delivery, modes of referral, facility and reporting and documentation. Conclusion: Several categories were identified, and reduction in these through discussions and iterative voting at workshops and consensus conferences is needed before finalizing the reporting set. LAY ABSTRACT A goal of this Delphi study was to identify the most important parameters of the International Classification of Service Organization in Rehabilitation (ICSO-R 2.0), to characterize rehabilitation services and identify important missing categories needed in a minimum reporting set. The most important and relevant factors for developing a minimum reporting set regarding the provider were: human resources, context, technical resources, quality assurance and management, location of provider, and ownership. Regarding service delivery the most important and relevant factors were: target group, rehabilitation team, aspect of time and intensity, setting, location of service delivery, modes of referral, facility and reporting and documentation. These factors should be discussed further, and a final set should be developed in workshops through discussion and iterative voting.